Temperature Dependence of the Breeding Parametres of the Collared Flycatcher (Passeriformes, Muscicapidae) in the National Park Homilshanski Lisy (NE Ukraine) - Atemasov, A. A.; Atemasova , T. A. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2024)
The breeding phenology of Collared Flycatchers was studied over an 11-year period (2006‒2011 and 2013‒2017) in oak-maple-lime stands located in the Northern-East of Ukraine (in the National Park Homilshanski Lisy). In most years, egg laying began in the first and second ten-day periods of May. The earliest recorded first-egg date (368 broods) was 23 April, while the latest was 5 May. These dates varied from year to year. The relationship between the first-egg date and the date of daily average temperature transition through + 10 °C suggests that birds bred earlier due to warmer local temperatures. The clutch size was negatively correlated with the date of the average air temperature transition through + 5 °C. The earliest hatching date was 15 May, and the latest was 25 May. Fledging typically began in the first half of June. The breeding season’s length ranged from 30 to 42 days, and the breeding cycle was positively correlated with the transition of the average daily temperature through +5 °C. To determine which factors explained the first egg date and clutch size, Generalized Linear Models (GLMs) were conducted. GLMs suggest a correlation between the first-egg date and the sum of effective temperatures (∑T150), arrival date temperature, migration route temperature, and average temperature of the third decade of April. Clutch size is determined by the sum of effective temperature accumulation (∑130) and migration route temperature. Reproductive success is negatively correlated with the average of 30 daily temperatures until the median date.